De ontwikkelingsgeschiedenis van Rein van Bemmelens (1904-1983) undatietheorie: veertig jaar Nederlandse geologie - Barzilay, Willemjan (Studium, 2009)
The development of Rein van Bemmelens (1904-1983) undation theory: Forty years of Dutch geology The Dutch geologist Rein van Bemmelen was the greatest opponent of plate tectonics in the Netherlands. He lived and worked during an important period in the history of earth sciences. He had studied geology when Wegeners theory was introduced and enthusiastically received in the Netherlands and he worked as a geologists during the period in which, after Wegeners theory was rejected in the Netherlands, several Dutch geologists came with their own theories to explain the origin of continents and oceans and in which plate tectonics was introduced in the Netherlands. He had proposed his own theory, the undation theory, at the beginning of the 1930s and kept on developing it during the following years. He continued to do so until his death in 1983. The history of the undation theory thus sheds light on the history of geology in the Netherlands. I will trace the history of geology in the Netherlands using Rein van Bemmelen and his undation theory as a lense.